Integrating Cash Waqf into Indonesia’s Free Meal Program Using the Business Model Canvas (BMC) - Hendriansyah Joe; Hendri Tanjung (AL-FALAH : Journal of Islamic Economics, 2025)
Purpose: This paper explores how Cash Waqf can support Indonesia’s free school meal program by applying the Business Model Canvas (BMC) framework to organize resources, stakeholders, costs, and benefits. Design/Method/Approach: Using a descriptive-qualitative approach, the study draws on secondary data from literature, case studies, and global practices in Islamic social finance. Lessons from the Nordic Pro-Meal initiative and Bangladesh’s BRAC program, both proven to enhance children’s health and learning, are adapted. The BMC is applied to map key partnerships, value propositions, activities, and financial flows for incorporating Cash Waqf into Indonesia’s free meal initiative. Findings: The proposed BMC involves collaboration between government, Islamic finance institutions, NGOs, and private partners. Key activities include fundraising, investment management, program implementation, and community engagement. Value propositions deliver sustainable charity for donors, nutritious meals for students, fiscal relief for government, and stronger social cohesion. Essential resources comprise Cash Waqf funds, human capital, infrastructure, and digital platforms. Costs include operational, technological, and outreach expenses, while revenues stem from Cash Waqf contributions, investment returns, sponsorships, and government support. Findings show Cash Waqf offers a scalable and sustainable funding mechanism to improve nutrition, education, and national development. Originality/Value: This study is the first to examine Cash Waqf’s role in Indonesia’s free school meal program. It contributes an innovative BMC framework demonstrating how Islamic social finance can be leveraged to enhance welfare and educational outcomes sustainably.